Ask me anything: Rafal Janik. (1st February 2023) - Tesh, Sarah
Abstract : Rafal Janik is the chief operating officer at the photonic quantum technology company Xanadu in Toronto, Canada. Founded in 2016, Xanadu has become one of the world's leading quantum hardware and software companies.